A combined experimental and numerical investigation on the scaling laws for steel box structures subjected to internal blast loading. (April 2017) - Yao, Shujian; Zhang, Duo; Lu, Fangyun; Chen, Xuguang; Zhao, Pengduo
Highlights: We designed three sets of steel box structures using "Replica" scaling law. We investigated steel box structures under internal blast through experiments. Scaling dynamic deformation was obtained. The reasons for imperfect similarity were discussed. Correction of the traditional scaling law for steel box structure was conducted. Abstract: The present work aims at the problem of scaling the deformation of steel box structures subjected to internal blast loading through experimental and numerical investigations. Three sets of steel box model with different scale-down factors were designed according to the geometrical similarity law ("Replica"), with three different explosive masses considered in each set based on Hopkinson's scaling law. The numerical results show good agreement with the experiments, and the results present that outward bulging produced in all sides and inplane buckling in the central area of boundary plate. And imperfect similarity was observed through comparing the plate center deflections though the deformation shapes present good similarity. The observed scale values are larger than those of geometry scale, and the difference increases with the increasing of geometry scale. In addition, the reasons for the deviation of the traditional scaling law were discussed. And then, based on the experimental results, correction of the scaling law for steel box structure was conducted which considered both the scale-down factor (size effect) and the scale distance (strain-rate effect).